Bahan Ajar Matematika Berbasis Problem Based Learning Sebagai Pendukung Pembelajaran Statistika - Puput Indriyani Nur Haeni; Nurhikmayati, Iik (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to develop mathematics teaching materials using the Problem-Based Learning (PBL) model on statistics topics, specifically measures of central tendency (mean, median, mode). Understanding mathematical concepts is crucial, yet many students in Indonesia still face difficulties in this area. The method used is Research and Development (R&D) with the ADDIE approach, which includes analysis, design, development, implementation, and evaluation. The research instruments consist of expert validation sheets for media and materials and practicality sheets for teachers and students. Data analysis was conducted by calculating the percentages of validity and practicality based on a Likert scale. The results indicate that the developed teaching materials have a validity score of 78.2%, which is in the valid category. These teaching materials are also highly practical for teachers and students, with a practicality score of 85.55%. The success of this study is supported by the use of the PBL model, which encourages students to actively engage in the learning process actively, thus enhancing their motivation and enthusiasm for understanding mathematical concepts. Although this study did not reach the implementation stage, the development results demonstrate the potential for improving student engagement in mathematics learning. Furthermore, this study can serve as a reference for teachers in designing more interactive and contextual teaching materials, providing a strong foundation for students' understanding of mathematical concepts in the future. Therefore, developing these teaching materials can positively contribute to the mathematics learning process in the classroom.